The new encyclopedia britannica in 30 volumes, macropedia Volume 6 / William Benton - Benton, William (1977)
Historical review, world geodetic system, international reference systems, factors involved in earth history, beginnings of earth history, Precambrian history, Paleozoic history, Mesozoic history, Cenozoic history, definition of gravity, measurement of gravity, interpretation of gravity data, sources of the earth´s heat, geological aspects of flow.